Operationalizing sense of place to evaluate potential conflicts in natural resource-dependent rural economies. Issue 4 (4th July 2021) - Ignatiadis, Mary; Daigneault, Adam; Sponarski, Carly; Reed, Joey
ABSTRACT: This paper investigates possible opportunities for consensus-building using survey data from the Katahdin Region, Maine. The region is primarily known for its abundance in forest-based manufacturing and recreation opportunities and is undergoing a major transition in its regional economy. We do this by applying the sense of place (SOP) framework to test the utility of SOP for understanding the development priorities. We identify the key similarities and differences in SOP between and within demographic groups that might lead to conflicts. Our results can be used to target outreach and facilitation activities to effectively build regional consensus, particularly with respect to targeting economic development. This approach presents a nuanced, yet intuitive picture of regional socioeconomic concerns with significant utility for development practitioners.